READING LITERATURE, TAKING PHILOSOPHICAL IDEAS, AND OBTAINING CHARACTERS - Maisaroh, Siti (OKARA: Jurnal Bahasa dan Sastra, 2017)
This study aims to describe the philosophical ideas and characters containing in trilogy of ’RaraMendut’s’ novel by YB Mangunwijaya.Â The method used is the knowledge archeology of Michel Foucault. The research proves that the philosophical ideas as follows: 1) wife’s faithfulness contains characters of wifeâ€™s strong determination and true faithfulness sense;Â 2) The women seizing fate’s Â contains the character of high struggle spirit;3) women as a gloryâ€™s symbol contains character of self-actualization ability;Â 4) women and a country’s defense contains a character of clever to take on the role / responsive;Â 5) women and their benefits contains the character as a source of love and life spirit;Â 6) women as good mothers contains the character of conciliatory, reassuring, joyful, sincere, and full of love;Â 7) the anxiety to old age contains the character of religious and strong self-awareness;Â 8) the glory contains the character of the glory of battle with themselves;Â 9) the child’s nature contains the character of belief in the skill/ creativity of children and believe to God the Evolver;Â And 10) the essence of wisdom and usefulness of life contain Â the characters of uniting the scattered things, receiving and embracing sincerely things bad/ broken/ waste, understanding and forgiving, voice sincerity and excitement, not easy to complain.